2017 Global Internet of Things Summit (GIoTS) 2017
DOI: 10.1109/giots.2017.8016251
|View full text |Cite
|
Sign up to set email alerts
|

GPS-free geolocation using LoRa in low-power WANs

Abstract: Abstract-Internet of Things (IoT) has been growing over the last few years in multiple applications and due to the high need GPS for tracking capabilities, an innovative opportunity arises. This paper reports on a design and implementation of a LoRaWAN tracking system which is capable exploiting transmitted packages to calculate the current position without the use of GPS or GSM. This is done using the low power technology LoRa where the geolocation is calculated applying a multilateration algorithm on the gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(83 citation statements)
references
References 3 publications
1
74
0
4
Order By: Relevance
“…This additional information may be combined with various information from other sources such as the Time delay of arrival (TDoA) to improve the accuracy of the localization of LoRa devices. Indeed, traditional LoRa localization techniques based on TDoA lack in precision when multipath is present and rely on complex fine‐grained synchronization …”
Section: Lpwan Mimo Range Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…This additional information may be combined with various information from other sources such as the Time delay of arrival (TDoA) to improve the accuracy of the localization of LoRa devices. Indeed, traditional LoRa localization techniques based on TDoA lack in precision when multipath is present and rely on complex fine‐grained synchronization …”
Section: Lpwan Mimo Range Extensionmentioning
confidence: 99%
“…Indeed, traditional LoRa localization techniques based on TDoA lack in precision when multipath is present and rely on complex fine-grained synchronization. 4 Regarding leveraging spatial diversity in LPWANs, previous work has proposed combining signals from an end device arriving at several gateways in the cloud in order to improve the SNR and thus increase the range of the uplink. The approach described in this paper, supporting a second antenna at the gateway allows to improve the range in the uplink direction, while saving bandwidth between gateways and the cloud infrastructure.…”
Section: Lpwan Mimo Range Extensionmentioning
confidence: 99%
“…Although their study reported positioning error exceeding 300 m, it was meaningful in that it showed that TDoA-based positioning was possible with LoRa signals. Fargas et al reduced the positioning error to ~100 m by adopting an iterative algorithm in their method [3].…”
Section: Fingerprint-algorithm-based Positioningmentioning
confidence: 99%
“…We adopted a Maximum Likelihood Estimation approach to estimate the locations of the end-device [11,12,22]. We can define a posterior probability Pr(l i |o * ) and likelihood probability function Pr(o * |l i ) as given by Equation (3). Pr(l i ) is the prior probability, and we set Pr(l i ) as a uniform distribution for experiments.…”
Section: Probability Map Generation and Positioningmentioning
confidence: 99%
See 1 more Smart Citation